California Residents’ Perceptions of Gene Drive Systems to Control Mosquito-Borne Disease - Schairer, Cynthia E.; Triplett, Cynthia; Akbari, Omar S.; Bloss, Cinnamon S. (Frontiers in Bioengineering and Biotechnology, 2022)
Scientists developing gene drive mosquitoes for vector control must understand how residents of affected areas regard both the problem of mosquito-borne disease and the potential solutions offered by gene drive. This study represents an experiment in public engagement at an early stage of technology development, intended to inform lab scientists about public attitudes toward their research and inspire consideration and conversation about the social ramifications of creating mosquitoes with gene drive. Online focus groups with California residents explored views on mosquito-borne disease risk, current mosquito control methods, and the proposed development and use of different classes of gene drives to control Ae. aegypti. Rather than a dogmatic rejection of genetic engineering or gene drive, many participants expressed pragmatic concerns with cost, control, the ability to narrowly target specific species, and the challenges of mistrust and institutional cooperation. Work like this is required to better align and balance professional and community priorities.